Paleomagnetism of the Circum-Ungava Proterozoic Fold Belt (I): Cape Smith Komatiitic Basalts - Fujiwara, Y.; Schwarz, E. J. (Canadian Journal of Earth Sciences, 1975)
A total of 397 oriented cores were taken from pillowed, columnar, and massive basalt of Cape Smith Island in northeastern Hudson Bay and from the adjacent mainland coast of Quebec. The thick series of basalts form part of the Circum-Ungava Proterozoic Belt which is of Aphebian (early Proterozoic) age. The lower portion of the basalt series contains pyrrhotite (Fe 7 S 8 ) and did not yield useful paleomagnetic results. The magnetization of the upper portion of the series is carried by small quantities [Formula: see text] of magnetite. The directions of magnetization of the samples do not change much during alternating field and thermal washing, and show very good grouping. The available internal evidence on the age of the stable remanence is inconclusive. The pole position (20°N, 162°E, semi-axes of the 95% oval of confidence: 4 °and 5°) after correcting for tilt is about 70° west of the preHudsonian part of the polar wandering curve established from North American data. The uncorrected pole position (16°N, 107°W), which would apply if the magnetization was acquired at the time of the Hudsonian orogeny, is in the general area of paleomagnetic poles for rocks of similar age from other localities of the Canadian Shield.